2005
DOI: 10.1007/s10350-004-0787-5
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Magnetic Resonance Imaging for Locally Advanced Rectal Carcinoma After Preoperative Chemoradiation Therapy

Abstract: Magnetic resonance imaging is commonly used in staging of pelvic malignancies because of its fine resolution, but chemoradiotherapy may decrease its accuracy. Thickening of the rectal wall after radiation by marked fibrosis, and peritumoral infiltration of inflammatory cells and vascular proliferation may contribute to overestimation of stage. By contrast, pathologic residual cancer beneath normal mural structure after chemoradiation therapy may result in understaging of rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
74
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(88 citation statements)
references
References 34 publications
10
74
2
2
Order By: Relevance
“…We were unable to measure the pretreatment-staging accuracy as all patients had chemoradiotherapy. Our postchemoradiotherapy MRI accuracy was consistent with other reports of 37%, 47% and 52% following long-course chemoradiotherapy [3,4,7]. There was poor agreement between postchemoradiotherapy radiological and pathological stages, which is less than some other studies reporting j = 0.4 [7].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…We were unable to measure the pretreatment-staging accuracy as all patients had chemoradiotherapy. Our postchemoradiotherapy MRI accuracy was consistent with other reports of 37%, 47% and 52% following long-course chemoradiotherapy [3,4,7]. There was poor agreement between postchemoradiotherapy radiological and pathological stages, which is less than some other studies reporting j = 0.4 [7].…”
Section: Discussionsupporting
confidence: 62%
“…Preoperative chemoradiation (CRT) is used in advanced local and ⁄ or nodal disease where it can lead to downstaging or complete response in up to 20% [1][2][3][4]. Magnetic resonance imaging (MRI) is now considered by many as the imaging modality of choice in staging rectal cancer [5].…”
Section: Introductionmentioning
confidence: 99%
“…After neoadjuvant CRT for rectal cancer, however, changes such as rectal muscular wall fibrosis, rectal mucosal oedema and peritoneal fibrosis make the detection of residual viable tumour difficult. Several investigators [9,10] have demonstrated overall tumour staging accuracy following CRT in the range 47-52%, indicating the difficulties of differentiating fibrosis from residual viable tumour with only morphological imaging using T2WI after CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Although MRI is considered the most accurate tool for primary tumour staging in rectal cancer [5][6][7], this modality has intrinsic limitations in the differentiation of residual viable tumour from surrounding fibrosis after neoadjuvant CRT of rectal cancer [8][9][10]. With the introduction of higher field-strength MR scanners and the parallel imaging technique for rectal MRI, diffusionweighted imaging (DWI) has been shown to have several potential benefits for the assessment of tumour localisation and staging [11,12].…”
mentioning
confidence: 99%
“…The accuracies of N staging for the MRI sets were equal (57%) ( Table 2). The overall accuracy of MR imaging in predicting T staging has been reported from 71%-91% (mean, 85%), and the range of overall accuracy of MR imaging in predicting N staging was 43%-85% (mean, 75%) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Resultsmentioning
confidence: 99%